2023
DOI: 10.1007/s13365-023-01133-3
|View full text |Cite
|
Sign up to set email alerts
|

iPSC-derived three-dimensional brain organoid models and neurotropic viral infections

Abstract: Progress in stem cell research has revolutionized the medical field for more than two decades. More recently, the discovery of induced pluripotent stem cells (iPSCs) has allowed for the development of advanced disease modeling and tissue engineering platforms. iPSCs are generated from adult somatic cells by reprogramming them into an embryonic-like state via the expression of transcription factors required for establishing pluripotency. In the context of the central nervous system (CNS), iPSCs have the potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 143 publications
0
7
0
Order By: Relevance
“…Brain cells infected with ZIKV can release MMP-2, destroying intercellular connection proteins and increasing vascular permeability [ 92 ]. Previous studies have shown that ZIKV can infect primary human brain endothelial cells and release the virus from the basolateral side, indicating a potential pathway for viral entry into the brain [ 99 , 100 ]. The comprehensive in vivo models have not yet elucidated the exact mechanism by which ZIKV infiltrates the brain.…”
Section: Zikv Pathophysiology Of Vascular Permeabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Brain cells infected with ZIKV can release MMP-2, destroying intercellular connection proteins and increasing vascular permeability [ 92 ]. Previous studies have shown that ZIKV can infect primary human brain endothelial cells and release the virus from the basolateral side, indicating a potential pathway for viral entry into the brain [ 99 , 100 ]. The comprehensive in vivo models have not yet elucidated the exact mechanism by which ZIKV infiltrates the brain.…”
Section: Zikv Pathophysiology Of Vascular Permeabilitymentioning
confidence: 99%
“…However, an in vitro model using differentiated brain endothelial cells has shown that ZIKV can cross the BBB with or without compromising its structural integrity [ 101 ]. Infection of astrocytes, which are closely associated with endothelial cells, is involved in BBB disruption [ 100 ] and provides a route for viral access to the brain. Nevertheless, the initial infection of astrocytes by ZIKV and the mechanisms underlying viral entry into the endothelial layers of the brain remain unclear [ 100 ].…”
Section: Zikv Pathophysiology Of Vascular Permeabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…iPSC- derived cells can be used as 2D and 3D cultures for CNS disease modeling, phenotypic assays, neural differentiation analysis, functional characterization, and cell migration studies, as well as cell therapies [ 253 , 254 , 255 , 256 , 257 ]. The potential of 3D brain organoids, derived from iPSCs, to replicate the CNS cell networks, shedding light on infections like HIV-1, HSV-1, and SARS-CoV-2 has been described [ 258 ]. Further, the establishment of choroid plexus organoids from hiPSCs showcased that SARS-CoV-2 infection led to heightened cell death and inflammatory response [ 259 ].…”
Section: The Use Of Ipsc-derived Cells In Neuroinflammatory Disease P...mentioning
confidence: 99%
“…Recent advances in stem cell technologies have opened up new possibilities for modeling and studying HAND, particularly the development of human iPSC derived neurons, astrocytes, and microglia capable of mimicking complex in vivo neuroimmune interactions when grown in three dimensional cerebral organoid cultures (Abud et al 2017;Ormel et al 2018;Xu et al 2021). Cerebral organoids offer a powerful and physiologically relevant platform to study complex neuroimmune interactions, but traditional organoid differentiation protocols do not produce microglia [reviewed in (Dos Reis, Sant, and Ayyavoo 2023;Swingler et al 2023;Wei et al 2023)]. Recent studies have demonstrated the feasibility of infecting iPSC-derived macrophages (Vaughan-Jackson et al 2021) and microglia (Rai et al 2020) with HIV-1.…”
Section: Introductionmentioning
confidence: 99%